Phytosterols Are Involved in Sclareol-Induced Chlorophyll Reductions in Arabidopsis - Asma Ben Hmidene; Hiroshi Ono; Shigemi Seo (Plants, 2023)
Sclareol, a diterpene, has a wide range of physiological effects on plants, such as antimicrobial activity; disease resistance against pathogens; and the expression of genes encoding proteins involved in metabolism, transport, and phytohormone biosynthesis and signaling. Exogenous sclareol reduces the content of chlorophyll in Arabidopsis leaves. However, the endogenous compounds responsible for sclareol-induced chlorophyll reduction remain unknown. The phytosterols campesterol and stigmasterol were identified as compounds that reduce the content of chlorophyll in sclareol-treated Arabidopsis plants. The exogenous application of campesterol or stigmasterol dose-dependently reduced the content of chlorophyll in Arabidopsis leaves. Exogenously-applied sclareol enhanced the endogenous contents of campesterol and stigmasterol and the accumulation of transcripts for phytosterol biosynthetic genes. These results suggest that the phytosterols campesterol and stigmasterol, the production of which is enhanced in response to sclareol, contribute to reductions in chlorophyll content in Arabidopsis leaves.